2018
DOI: 10.1016/j.ejbas.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive potential of secondary metabolites derived from medicinal plant endophytes

Abstract: Medicinal plants have been used as an alternative medicine to promote human health and longevity in many regions of the world since ancient times. In recent years, many novel secondary metabolites from higher fungi have been isolated and reported to provide lead compounds for new drug discovery like antimicrobial, antioxidant, and anticancer agents, etc. A total of 42 endophytic fungi were isolated from 11 different medicinal plants collected from Tamil Nadu, India. The capability of medicinal plant endophytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 23 publications
4
47
0
Order By: Relevance
“…We observed a differential growth inhibition pattern of gram-positive by the ethyl acetate fraction containing the compound, 3-methyl, 4-oxo-pentanoic acid. Similarly, the zone of inhibition against gram-negative bacteria, R. eutropha was observed to be similar to that reported earlier of Alternaria sp (Palanichamy et al 2018). Interestingly, antifungal activity against candida albicans was not observed in the ethyl acetate fraction.…”
Section: Discussionsupporting
confidence: 88%
“…We observed a differential growth inhibition pattern of gram-positive by the ethyl acetate fraction containing the compound, 3-methyl, 4-oxo-pentanoic acid. Similarly, the zone of inhibition against gram-negative bacteria, R. eutropha was observed to be similar to that reported earlier of Alternaria sp (Palanichamy et al 2018). Interestingly, antifungal activity against candida albicans was not observed in the ethyl acetate fraction.…”
Section: Discussionsupporting
confidence: 88%
“…The secondary metabolites from A. alternata were screened and characterized for their antibacterial properties and antioxidant activity similar to our previous study (Palanichamy et al ). Here, in the present study the concentrated ethyl acetate extract of A. alternata MGTMMP031 was fractionated by standard column chromatographic technique.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the highest antibacterial activity of the fungal endophytes isolate ST9.1 was performed on day 4 with an inhibition zone of 12.67 ± 0.47 mm. The activity was highest on early fermentation suggested that such metabolism could lead to an increase metabolic products ( Adebo and Medina-Meza, 2020 ) and the diversity of metabolites synthesis were produced by various metabolic pathway ( Palanichamy et al, 2018b ). Noticeably, when the incubation time was increased, the function of bioactive molecule decreased ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Each solvent phase was collected and condensed using the rotary vacuum evaporator. The dry crude extract metabolite was obtained at 4 °C, kept at − 20◦C and 2% DMSO, respectively, for use in the future ( Palanichamy et al, 2018a ).…”
Section: Methodsmentioning
confidence: 99%